Perancangan Sistem Pendingin dan Tata Udara pada Ruang Mesin produksi di PT. X untuk Menjaga Performa dan Ketahanan Komponen Mesin: Installation of Refrigeration and Air Conditioning Systems in The Production Facility on PT. X to Maintain the Performance and Durability of Machine Components - Habibi Santoso (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
Several influencing factors, including temperature, air cleanliness, and humidity levels, are necessary to preserve the performance and durability of engine components against injury. Many mechanical and electrical components of the machine were damaged at Company X because the room's temperature, air quality, and humidity did not comply with the machine's standard operating conditions. If nothing is done to enhance the engine room's air conditioning, the engine will sustain greater damage. The purpose of this research is to design a cooling and air-conditioning system in the production machine space in PT. X to maintain the performance and durability of machine components. The engine compartment is 104 m2. The design of the refrigeration and air conditioning systems includes the calculation of the required capacity, analysis, and the creation of design drawings in the engine compartment. According to the calculation, the required engine room refrigeration capacity unit is 9.36 kW with 1640 l/s. This capacity incorporates the requirement for fresh air, which is 245 l/s. With this capacity, the engine's optimal temperature and oxygen quality can be attained.